Supporting Condition is an important factor in the behaviour of the façade system - Jeyamohan, K. (Annual Transactions, IESL Northern Chapter, 2021)
The Main task of this paper is to present the behaviour of the glass with various types of fixing methods, mainly discuss the stress & displacement variation of the glass under the loading with following fixing methods: Four side, two side & Point Fixing. Failure of the glass or required thickness of the glass mainly depending on the fixing methods. Mainly glass is fixed with supporting member by using either Structural Sealant (Four side & two side fixing) or Spider (Point Fixing). Mainly this Study is to analyse the stress & displacements pattern of the glass under different type of loading (Uniform Pressure, Line Loading & Point Loading) with above categorized support condition. In addition, Point Fixing Curtain wall (Glass) is required additional design concern to avoid the glass breakage at the contact surface of the Glass & spider.
Keywords: Point Fixing; Structural Sealant; Spider; Curtain Wall